Self-adhesive laminate

The self-adsorbing laminate, featuring an acrylic resin foam sheet with specific density and compressive strength, addresses the challenges of unevenness tracking and long-term adhesion stability, ensuring high conformity and reworkability while preventing resin residue.

JP7647098B2Active Publication Date: 2025-03-18ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020219543
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-03-18
Estimated Expiration
2040-12-28

AI Technical Summary

Technical Problem

Conventional self-adsorbing laminates struggle with unevenness tracking on surfaces with irregularities, leading to issues like floating, peeling, and remaining resin after long-term use.

Method used

A self-adsorbing laminate composed of a base material laminated with a self-adsorbing foam sheet made of acrylic resin foam, with a density between 0.3g/cm³ and 0.7g/cm³ and a 25% compressive strength of 3 kPa to 15 kPa, enhancing conformity with uneven surfaces, long-term adhesion stability, and reworkability.

Benefits of technology

The laminate achieves high conformity with uneven surfaces, maintains long-term adhesion stability, and improves reworkability by preventing resin residue and ensuring easy peeling without damaging the adherend.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647098000001
    Figure 0007647098000001
Patent Text Reader

Abstract

To provide a self-adsorptive laminate that achieves unevenness followability during pasting, long-term adhesion stability, and reworkability after long-term use at high level.SOLUTION: Provided is a self-adsorptive laminate, which is a self-adsorptive laminate formed by laminating a substrate and a self-adsorptive foam sheet made of an acrylic resin foam, and in which the density of the self-adsorptive foam sheet is 0.3 g / cm3 or more and 0.7 g / cm3 or less, and the 25% compressive strength of the self-adsorptive foam sheet is 3 kPa or more and 15 kPa or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a self-adhesive laminate. [Background technology]

[0002] Conventionally, a sheet-like member made of a foam material having a large number of fine pores and having self-adhesive properties, that is, a self-adhesive foam sheet (hereinafter, sometimes simply referred to as a "foam sheet"), has been used as an adhesive sheet to be attached to an adherend such as a wall or window glass. The adhesive mode of the self-adhesive foam sheet is not glue adhesion, but adhesion to the adherend using the fine pores. Therefore, the self-adhesive foam sheet is easier to reattach than the conventional adhesive sheet using glue adhesion, and is preferably used for applications such as wallpaper, posters, and stickers. When used for these applications, the self-adhesive foam sheet is usually used in the form of a self-adhesive laminate (hereinafter, sometimes simply referred to as a "laminate sheet") laminated with a substrate. By applying decoration such as printing to the surface of the substrate side of this self-adhesive laminate, it can be advantageously used for the above-mentioned applications.

[0003] For example, Patent Document 1 describes a self-adhesive laminate that can be attached to and removed from a plaster board or the like and has a density of 0.2 g / cm 3 More than 1.5g / cm 3 A graphic sheet is disclosed in which an adhesive layer made of the following open-cell foam is disposed on a base film layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-218561 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the above-mentioned conventional self-adhesive laminates had room for improvement in terms of being able to simultaneously exhibit excellent conformability to uneven surfaces, inhibit the occurrence of lifting or peeling during long-term use, and prevent resin from remaining on the adherend surface when peeled off after long-term use, when used by adhering to an uneven surface such as a wall surface covered with wallpaper.

[0006] Therefore, an object of the present invention is to provide a self-adhesive laminate that simultaneously achieves high levels of conformability to irregularities during application, long-term adhesion stability, and reworkability after long-term use. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and have found that by using a self-adhesive foam sheet made of an acrylic resin foam having a density and compressive strength both within a predetermined range, it is possible to simultaneously achieve high levels of conformability to unevenness during application, long-term adhesion stability, and reworkability after long-term use, and have completed the present invention.

[0008] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the self-adhesive laminate of the present invention is formed by laminating a substrate and a self-adhesive foamed sheet made of an acrylic resin foam, and the self-adhesive foamed sheet has a density of 0.3 g / cm 3 More than 0.7g / cm 3 The self-adhesive foam sheet is characterized in that its density is 3 kPa or more and its 25% compressive strength is 3 kPa or more and 15 kPa or less. In this way, when both the density and compressive strength of the self-adhesive foam sheet are within the predetermined ranges, it is possible to simultaneously achieve high levels of conformability to irregularities during application, long-term adhesion stability, and reworkability after long-term use. In the present invention, the "density" and "25% compressive strength" of the self-adhesive foam sheet can be measured by the methods described in the examples.

[0009] Here, in the self-adhesive laminate of the present invention, the self-adhesive foam sheet preferably has an average thickness of 0.05 mm or more and 1 mm or less. If the self-adhesive foam sheet has an average thickness of 0.05 mm or more and 1 mm or less, the unevenness-following ability can be further improved, and an increase in the self-adhesive weight and a decrease in workability can be suppressed. In the present invention, the "average thickness" of the self-adhesive foam sheet refers to the arithmetic mean value of thicknesses at any six points on the self-adhesive foam sheet.

[0010] In the self-adhesive laminate of the present invention, the acrylic resin foam is preferably formed of a cross-linked acrylic resin. If the acrylic resin foam is formed of a cross-linked acrylic resin, the generation of resin residue on the adherend surface during peeling can be further suppressed, and reworkability can be further improved.

[0011] Furthermore, in the self-adhesive laminate of the present invention, it is preferable that the acrylic resin foam contains a foam stabilizer, because the acrylic resin foam containing a foam stabilizer has a good open cell structure and can easily release air during application.

[0012] In addition, the self-adhesive laminate of the present invention preferably has a conforming rate of the self-adhesive foam sheet of 30% or more and 90% or less. If the conforming rate is equal to or more than the lower limit, the adhesion stability over a long period of time can be further improved. If the conforming rate is equal to or less than the upper limit, the occurrence of resin residue on the adherend surface during peeling can be further suppressed. In the present invention, the "irregularity-following rate" of the self-adhesive foam sheet can be measured by the method described in the examples.

[0013] Furthermore, in the self-adhesive laminate of the present invention, it is preferable that the initial self-adhesive strength of the self-adhesive foam sheet is 0.01 N / cm or more and 0.50 N / cm or less. If the initial self-adhesive strength is equal to or more than the lower limit, the self-adhesive laminate can be well attached to the adherend. If the initial self-adhesive strength is equal to or less than the upper limit, reworkability can be improved and damage to the adherend during peeling can be suppressed. In the present invention, the "initial self-adhesive strength" of the self-adhesive foam sheet can be measured by the method described in the Examples (self-adhesive strength (initial)).

[0014] In addition, in the self-adhesive laminate of the present invention, the self-adhesive strength of the self-adhesive foam sheet after accelerated testing is preferably 0.10 N / cm or more and 1.0 N / cm or less. If the self-adhesive strength after accelerated testing is equal to or more than the lower limit, adhesion stability over a long period of time can be sufficiently ensured. If the self-adhesive strength after accelerated testing is equal to or less than the upper limit, reworkability can be improved and damage to the adherend during peeling can be suppressed. In the present invention, the "self-adhesive strength after accelerated test" of the self-adhesive foam sheet can be measured by the method described in the Examples (self-adhesive strength (after accelerated test)).

[0015] Furthermore, the self-adhesive laminate of the present invention combines high levels of conformability to uneven surfaces during application, long-term adhesion stability, and reworkability after long-term use, and can therefore be suitably used for application to uneven surfaces such as wallpaper. Effect of the Invention

[0016] The self-adhesive laminate of the present invention can simultaneously achieve high levels of conformability to irregularities during application, long-term adhesion stability, and reworkability after long-term use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described in detail. Here, the self-adhesive laminate of the present invention is not particularly limited, and can be used by being attached to an uneven surface such as a wall surface covered with wallpaper, and can be easily peeled off from the surface after use.

[0018] (Self-adhesive laminate) The self-adhesive laminate of the present invention is formed by laminating a substrate and a self-adhesive foam sheet made of an acrylic resin foam. The self-adhesive laminate of the present invention has a density of 0.3 g / cm 3 More than 0.7g / cm 3 The present invention is characterized in that a self-adhesive foam sheet having a compressive strength of 3 kPa or more and 15 kPa or less is used. The structure of the self-adhesive laminate of the present invention is not particularly limited as long as the self-adhesive foam sheet is laminated on one side in the thickness direction of the substrate, and one surface (the surface to be attached to the adherend during use) is composed of the self-adhesive foam sheet. For example, the self-adhesive laminate may have a structure in which an arbitrary layer such as an adhesive layer is interposed between the substrate and the self-adhesive foam sheet.

[0019] Here, in general, in order to improve the unevenness conformability during application, it is necessary to use a soft self-adhesive foam sheet, but when a soft self-adhesive foam sheet is used, the resin is likely to remain on the adherend surface when the self-adhesive laminate is peeled off. In addition, in order to improve the long-term adhesion stability, it is necessary to use a self-adhesive foam sheet with high adhesive strength, but when a self-adhesive foam sheet with high adhesive strength is used, the resin is likely to remain on the adherend surface when the self-adhesive laminate is peeled off, and the adherend may be damaged. Therefore, there is usually a trade-off between the unevenness conformability during application, the long-term adhesion stability, and the reworkability after long-term use, and it is difficult to make them compatible with each other. However, in the self-adhesive laminate of the present invention, an acrylic resin foam having both density and 25% compression strength within a specific range is used as the self-adhesive foam sheet, so that the unevenness conformability during application, the long-term adhesion stability, and the reworkability after long-term use can be made to be compatible at a high level.

[0020] <Base material> The substrate is not particularly limited, and may be a paper substrate other than synthetic paper, a synthetic paper substrate, a plastic substrate, a fiber substrate, a metal substrate, a glass substrate, etc. The thickness of the substrate is not particularly limited, and may be, for example, 10 μm or more and 200 μm or less.

[0021] Examples of the paper base material include fine paper, art paper, coated paper, craft paper, and these paper base materials laminated with a thermoplastic resin such as polyethylene.

[0022] The synthetic paper base material is not particularly limited, but examples thereof include a synthetic paper base material having a surface layer made of paper by combining a thermoplastic resin and an inorganic filler.

[0023] Examples of plastic substrates include polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate; polystyrene-based resins; polyvinyl chloride-based resins; acrylic-based resins; polycarbonate-based resins; polyamide-based resins; fluorine-based resins such as polytetrafluoroethylene; and sheet-like substrates made of mixtures or laminates of these resins.

[0024] Examples of fiber substrates include natural fibers such as cotton and silk; polyamide-based synthetic fibers; polyester-based synthetic fibers; polypropylene-based synthetic fibers; polyvinyl chloride-based synthetic fibers; polyvinyl alcohol-based synthetic fibers; semi-synthetic fibers such as acetate; regenerated artificial fibers such as rayon; and sheet-like substrates made of mixtures or laminates of these fibers.

[0025] The metal substrate is not particularly limited, and examples thereof include sheet-like substrates made of metals such as iron, copper, aluminum, gold, platinum, and silver, as well as alloys or laminates of these metals.

[0026] The glass substrate is not particularly limited, and examples thereof include sheet-shaped substrates made of soda-lime glass, borosilicate glass, non-alkali glass, quartz glass, and the like.

[0027] <Self-adhesive foam sheet> The self-adhesive foam sheet has a density of 0.3g / cm 3 More than 0.7g / cm 3 and is made of an acrylic resin foam having a 25% compressive strength of 3 kPa or more and 15 kPa or less.

[0028] [Acrylic resin foam] The acrylic resin foam can be formed by foaming and molding a foam sheet composition containing an acrylic resin, and curing it as necessary. From the viewpoint of suppressing the occurrence of resin residue on the adherend surface during peeling and enhancing reworkability, the acrylic resin foam is preferably formed from a crosslinked acrylic resin.

[0029] The foam sheet composition used to form the acrylic resin foam may be a composition containing an acrylic resin and, optionally, one or more additives selected from the group consisting of a crosslinking agent, a foam stabilizer, a solvent, and other additives.

[0030] As the acrylic resin, a polymer containing a (meth)acrylate monomer unit and optionally further containing other monomer units can be used. In the present invention, the phrase "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer." In addition, in the present invention, "(meth)acrylate" means acrylate and / or methacrylate.

[0031] Here, the (meth)acrylate monomer unit is a repeating unit derived from a (meth)acrylate monomer. The (meth)acrylate monomer is not particularly limited, but examples thereof include (meth)acrylic acid alkyl ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-heptyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-dodecyl (meth)acrylate; (meth)acrylic acid alkoxy alkyl ester monomers such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, and ethoxymethyl (meth)acrylate; and the like. Among these, from the viewpoint of improving conformability to irregularities during application and long-term adhesion stability, it is preferable to use n-butyl acrylate and / or 2-ethylhexyl acrylate as the (meth)acrylate monomer. The (meth)acrylate monomers may be used alone or in combination of two or more. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic.

[0032] The proportion of (meth)acrylate monomer units in the polymer is preferably 60% by mass or more and 95% by mass or less, with all repeating units (all monomer units) contained in the polymer being 100% by mass.

[0033] The other monomer units are not particularly limited, and examples thereof include the monomer units described in International Publication No. 2018 / 151274. Specifically, the other monomer units are not particularly limited, and examples thereof include a repeating unit derived from an unsaturated carboxylic acid monomer, a repeating unit derived from a vinyl cyanide monomer, and a repeating unit derived from an alkenyl aromatic monomer. The acrylic resin preferably contains, as other monomer units, monomer units having a functional group capable of forming a crosslinked structure using a crosslinking agent described in detail below.

[0034] From the viewpoint of obtaining an acrylic resin foam that has excellent conformability to irregularities during application and excellent adhesion stability over a long period of time, it is preferable to use an acrylic resin having a low glass transition temperature, and it is more preferable that the glass transition temperature of the acrylic resin be −25° C. or lower. In the present invention, the "glass transition temperature" can be measured using a differential scanning calorimeter in accordance with JIS K7121 under conditions of a measurement temperature of -50°C or higher and 160°C or lower, and a heating rate of 10°C / min.

[0035] The crosslinking agent that can be blended in the foam sheet composition is not particularly limited as long as it is capable of crosslinking the acrylic resin, and examples of the crosslinking agent include epoxy-based crosslinking agents; carbodiimide-based crosslinking agents; oxazoline-based crosslinking agents; polyfunctional isocyanate-based crosslinking agents such as tolylene diisocyanate, trimethylolpropane tolylene diisocyanate, and diphenylmethane triisocyanate; metal salt-based crosslinking agents; metal chelate-based crosslinking agents; and peroxide-based crosslinking agents. Among them, the crosslinking agent is preferably an epoxy-based crosslinking agent or an oxazoline-based crosslinking agent.

[0036] The amount of the crosslinking agent is not particularly limited, and can be 0.1 to 10 parts by mass per 100 parts by mass of the acrylic resin. If the amount of the crosslinking agent is equal to or greater than the lower limit, the strength of the acrylic resin foam can be ensured, and the occurrence of resin residue on the adherend surface during peeling can be suppressed. If the amount of the crosslinking agent is equal to or less than the upper limit, the flexibility of the acrylic resin foam can be ensured, and the unevenness-following ability during attachment and the long-term adhesion stability can be improved.

[0037] The foam stabilizer that can be blended in the composition for foam sheet may be a known foam stabilizer such as a higher fatty acid salt or a surfactant. The foam stabilizer may remain in the acrylic resin foam formed using the composition for foam sheet.

[0038] The amount of the foam stabilizer is not particularly limited and can be from 0.1 to 20 parts by mass per 100 parts by mass of the acrylic resin. When the amount of the foam stabilizer is equal to or more than the lower limit, an acrylic resin foam having a good open-cell structure can be obtained.

[0039] The solvent that may be optionally contained in the foam sheet composition of the present invention is not particularly limited, and examples thereof include water and organic solvents, with water being preferred.

[0040] Examples of other additives that can be blended in the foam sheet composition include foaming assistants, thickeners, fillers, preservatives, antifungal agents, gelling agents, flame retardants, antioxidants, antioxidants, pigments, dyes, tackifiers, conductive compounds, water-resistant agents, oil-resistant agents, etc. The above-mentioned other additives are not particularly limited, and known additives, such as those described in International Publication No. 2016 / 147679, can be used.

[0041] The formation of an acrylic resin foam using the above-mentioned foam sheet composition is not particularly limited, and can be carried out, for example, by foaming a prepared foam sheet composition to obtain a foam in an uncured (uncrosslinked) state, forming the foam into a sheet, and curing (crosslinking reaction) as necessary.

[0042] Here, the foam sheet composition can be prepared by mixing the above-mentioned components in any method and order. For example, when an acrylic resin latex is used to prepare the foam sheet composition, a crosslinking agent, a foam stabilizer, other additives, etc. may be added to the latex as necessary and mixed by a known method. When a solid acrylic resin is used to prepare the foam sheet composition without using a solvent, the solid acrylic resin may be mixed with a crosslinking agent, a foam stabilizer, other additives, etc., which are added as necessary, by a known method (for example, using a known roll, Henschel mixer, kneader, etc.).

[0043] The viscosity of the foam sheet composition containing a solvent (e.g., in the form of an emulsion or dispersion) is preferably 1,000 mPa·s or more, more preferably 2,000 mPa·s or more, even more preferably 3,500 mPa·s or more, and preferably 10,000 mPa·s or less, more preferably 5,500 mPa·s or less. If the viscosity of the foam sheet composition is 1,000 mPa·s or more, it is possible to prevent dripping that makes it difficult to control the thickness when coating a foam formed from the foam sheet composition on a substrate or the like. On the other hand, if the viscosity of the foam sheet composition is 10,000 mPa·s or less, it is also possible to prevent difficulty in controlling the expansion ratio by mechanical foaming when forming a foam sheet. The viscosity of the foam sheet composition can be measured at a temperature of 23° C. using a Brookfield type viscometer.

[0044] In addition, as a method for foaming the composition for foaming sheets, it is preferable to adopt mechanical foaming from the viewpoint of obtaining an acrylic resin foam having excellent flexibility. The foaming ratio may be appropriately adjusted, but is preferably 1.5 times or more, more preferably 1.6 times or more, and is also preferably 2.2 times or less, more preferably 2.0 times or less. If the foaming ratio is equal to or more than the above lower limit, an acrylic resin foam having excellent unevenness-following ability during attachment and excellent adhesion stability over a long period of time can be obtained. If the foaming ratio is equal to or less than the above upper limit, the occurrence of resin residue on the adherend surface during peeling can be suppressed.

[0045] The mechanical foaming can be carried out by, but not limited to, mixing a certain amount of air into the emulsion or dispersion of the foamed sheet composition and stirring continuously or batchwise with an oak mixer, whipper, etc. The foam thus obtained (foamed emulsion or foamed dispersion) is creamy.

[0046] Furthermore, the method of forming the foam into a sheet is not particularly limited. A suitable method is, for example, a method of coating the foam onto a desired substrate and forming it into a sheet. In this way, by coating the foam onto a desired substrate and allowing the crosslinking reaction to proceed, a laminated sheet in which the foam sheet is directly provided on the substrate can be obtained.

[0047] The foam coating can also be performed on a release sheet (such as a release-capable processing paper) instead of the above-mentioned substrate. If the foam is coated on the release sheet and a crosslinking reaction is allowed to proceed, a laminate in which the foam sheet is provided directly on the release sheet can be obtained. Then, by peeling the release sheet from the foam sheet of this laminate, the foam sheet can be obtained alone (as an independent film).

[0048] As a method for coating the foam onto a substrate or a release sheet (hereinafter, these may be collectively referred to as "substrate, etc."), a commonly known coating device such as an applicator, a bar coater, a roll coater, a reverse roll coater, a screen coater, a doctor knife coater, or a comma knife coater can be used.

[0049] A method for crosslinking a foam molded into a sheet is preferably a method for heating and drying the foam. The method for heating and drying is not particularly limited as long as it is a method capable of drying and crosslinking a foam molded into a sheet, and a known drying oven (for example, a hot air circulation type oven, a hot oil circulation hot air chamber, a far infrared heater chamber) can be used. The drying temperature can be, for example, 60°C or higher and 180°C or lower. It is preferable to perform multi-stage drying such that drying is performed from the inside at a low temperature in the early stage of drying and is sufficiently dried at a higher temperature in the later stage of drying, rather than performing drying at a constant temperature.

[0050] The laminate of the acrylic resin foam and the substrate or the like obtained as described above is not particularly limited, but for example, after a separator film is attached to the self-adhesive surface, it can be wound up by a winder and cut to an easy-to-use size by press cutting, a slitter, or the like.

[0051] [density] The density of the self-adhesive foam sheet made of acrylic resin foam is 0.3 g / cm 3 More than 0.7g / cm 3 It must be less than 0.4g / cm 3 More than 0.55g / cm 3 It is preferable that the density is equal to or less than the upper limit. If the density is equal to or less than the upper limit, the self-adhesive foam sheet has a suitable flexibility, and the sheet can improve its ability to conform to uneven surfaces during application and its long-term adhesion stability. If the density is equal to or more than the lower limit, the self-adhesive foam sheet has a suitable strength, and the sheet can suppress the occurrence of resin residue on the adherend surface during peeling.

[0052] [25% compressive strength] The 25% compressive strength of the self-adhesive foam sheet made of acrylic resin foam must be 3 kPa or more and 15 kPa or less, preferably 4 kPa or more, more preferably 4.5 kPa or more, preferably 10 kPa or less, and more preferably 8 kPa or less. If the 25% compressive strength is equal to or less than the upper limit, the self-adhesive foam sheet can have a suitable flexibility, and can improve the unevenness-following ability during application and the long-term adhesion stability. If the 25% compressive strength is equal to or more than the lower limit, the self-adhesive foam sheet can have a suitable strength, and can suppress the occurrence of resin residue on the adherend surface during peeling.

[0053] [Unevenness tracking rate] Furthermore, the self-adhesive foam sheet made of acrylic resin foam has a conformability to unevenness of preferably 30% or more, more preferably 40% or more, and preferably 90% or less, and more preferably 85% or less. If the conformability to unevenness is equal to or greater than the lower limit, the adhesion stability over a long period of time can be improved. If the conformability to unevenness is equal to or less than the upper limit, the occurrence of resin residue on the adherend surface during peeling can be suppressed. Here, if the adhesive strength of the self-adhesive foam sheet is increased so that it can adhere well to an uneven surface, it is likely to damage a fragile adherend such as wallpaper when peeled off, whereas if the adhesive strength is low, it will not adhere to the uneven surface. Therefore, it is effective from the viewpoint of adhesion stability and protection of the adherend to increase the unevenness-following rate to ensure a contact area with the adherend without increasing the adhesive strength.

[0054] [Initial self-adhesion strength] The initial self-adhesive strength of the self-adhesive foam sheet made of acrylic resin foam is preferably 0.01 N / cm or more, more preferably 0.05 N / cm or more, and preferably 0.50 N / cm or less, and more preferably 0.30 N / cm or less. If the initial self-adhesive strength is equal to or greater than the lower limit, the self-adhesive laminate can be well attached to the adherend. If the initial self-adhesive strength is equal to or less than the upper limit, damage to the adherend during peeling can be suppressed even when the self-adhesive laminate is attached to a fragile adherend such as wallpaper.

[0055] [Self-adhesion after accelerated testing] In addition, the self-adhesive strength of the self-adhesive foam sheet made of acrylic resin foam after accelerated testing is preferably 0.10 N / cm or more, more preferably 0.20 N / cm or more, preferably 1.0 N / cm or less, and more preferably 0.70 N / cm or less. If the self-adhesive strength after accelerated testing is equal to or greater than the lower limit, adhesion stability over a long period of time can be sufficiently ensured. If the self-adhesive strength after accelerated testing is equal to or less than the upper limit, reworkability can be improved, and even when the sheet is attached to a fragile adherend such as wallpaper, damage to the adherend during peeling can be suppressed.

[0056] Average Thickness The self-adhesive foam sheet made of acrylic resin foam has an average thickness of preferably 0.05 mm or more, more preferably 100 μm or more, and preferably 1 mm or less, and more preferably 500 μm or less. If the average thickness is equal to or greater than the lower limit, the sheet can improve the conformability to unevenness during application and can prevent the uneven shape of the adherend surface from being transferred to the substrate. If the average thickness is equal to or less than the upper limit, the sheet can prevent the weight from increasing and improve workability.

[0057] The properties (density, 25% compressive strength, unevenness conformance rate, average thickness, self-adhesive strength, etc.) of the acrylic resin foam described above can be adjusted, for example, by changing the composition and solids concentration of the foam sheet composition, the ratio of air bubbles mixed in during foaming, the thickness of coating the foam, and the drying and crosslinking conditions.

[0058] <Method of manufacturing self-adhesive laminate> When the self-adhesive foam sheet made of the above-mentioned acrylic resin foam is molded on a substrate, the resulting laminate can be used as a self-adhesive laminate as is, or after being processed, such as cut, as necessary. Furthermore, when the self-adhesive foam sheet made of the above-mentioned acrylic resin foam is molded on a release sheet, the self-adhesive foam sheet peeled off from the release sheet can be laminated and integrated with a substrate to obtain a self-adhesive laminate. Here, the self-adhesive foam sheet and the substrate can be integrated by known techniques such as the use of adhesives, fusion bonding, and pressure bonding.

[0059] <Applications of self-adhesive laminates> The substrate surface of the self-adhesive laminate may be printed by, for example, offset printing, seal printing, flexographic printing, silk screen printing, gravure printing, a laser printer, a thermal transfer printer, an inkjet printer, etc. The substrate of the self-adhesive laminate may be decorated. The self-adhesive laminate can be advantageously used as a sheet to be attached to an uneven surface, such as wallpaper to be attached on top of wallpaper, without any particular limitation. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified. In the examples and comparative examples, the density, 25% compressive strength, and unevenness conformance rate of the self-adhesive foam sheet, as well as the self-adhesive strength (initial and after accelerated testing), adhesion stability, and reworkability of the self-adhesive laminate were evaluated by the following methods.

[0061] <density> The self-adhesive laminate was cut to a size of 20 cm x 20 cm to prepare a test piece. The mass of the cut test piece: Xg was precisely weighed. In addition, the mass of the substrate cut to 20 cm x 20 cm: Yg was precisely weighed. Thereafter, the thicknesses of the self-adhesive laminate and substrate prepared were measured with a thickness gauge, and the thickness of the substrate was subtracted from the thickness of the self-adhesive laminate to obtain the thickness of the self-adhesive foam sheet: Tcm. At this time, the thickness value was calculated from the average value of six measurements. The measured values ​​of X, Y, and T were substituted into the following formula to calculate the density of the self-adhesive foam sheet. Density (g / cm 3 )=(XY) / (T×20×20) <25% Compressive Strength> A self-adhesive foam sheet was cut from the self-adhesive laminate to a size of 25 mm x 25 mm x 20 mm to prepare a test piece. Then, in accordance with JIS K6254, the stress value (kPa) when compressed to 25% of the initial thickness at a speed of 10 mm / min using an autograph (manufactured by Shimadzu Corporation, "AG-IS") was measured, and this was taken as the 25% compression strength. <Irregularity tracking rate> The self-adhesive laminate was cut into a size of 125 mm x 25 mm to prepare a test piece. The test piece was then attached to a wallpaper (manufactured by Lilycolor Co., Ltd., "LB-9424") cut into a size of 125 mm x 50 mm, and a load of 2 kgf was applied from above the test piece to press the wallpaper and the test piece together with a roller. Next, the test piece attached to the wallpaper was cut from above with a razor blade so that the cross section (adhesive surface) was exposed, and the cross section was observed with a digital microscope (Keyence Corporation, "VHK-6000") and the contact rate between the wallpaper surface and the self-adhesive foam sheet of the test piece (= (cross-sectional length of the self-adhesive foam sheet adhered to the wallpaper / cross-sectional length of the wallpaper surface) x 100%) was recorded as the unevenness-following rate (%). <Self-adhesive strength (initial)> The self-adhesive laminate thus prepared was cut into a size of 125 mm x 25 mm to prepare a test piece. Next, wallpaper (manufactured by Lilycolor Co., Ltd., "LB-9424") cut into a size of 125 mm x 50 mm was attached to an aluminum plate of the same size with double-sided tape to prepare an adherend. The self-adhesive foam sheet side of the test piece was attached to the wallpaper side of the adherend, and a load of 2 kgf was applied from above the test piece to press it with a roller, and the test piece was left for 1 hour under an environment of 23 ° C. and 50% RH. Then, the end of the test piece was fixed to the upper chuck of an autograph (manufactured by Shimadzu Corporation, "AG-IS"), the adherend was fixed to the lower chuck, and a 180-degree peel test was performed at a speed of 300 mm / min under an environment of 23 ° C. and 50% RH. The peel force (N / cm) at this time was taken as the self-adhesive force (initial) to the adherend. <Self-adhesion (after accelerated testing)> The test piece and the adherend were prepared in the same manner as in the measurement of the "self-adhesive strength (initial)" above. The self-adhesive foam sheet side of the test piece was attached to the wallpaper side of the adherend, and the test piece was pressed with a roller under a load of 2 kgf from above, and left for 3 hours under an environment of 23 ° C and 50% RH. Then, the test piece was left for 14 days in a thermostatic chamber (manufactured by ESPEC, "CSH-111") adjusted to 60 ° C and 80% RH (accelerated test). After 14 days, the bonded body of the test piece and the adherend was removed from the thermostatic chamber and left for 3 hours under an environment of 23 ° C and 50% RH, and then the end of the test piece was fixed to the upper chuck of an autograph (manufactured by Shimadzu Corporation, "AG-IS"), the adherend was fixed to the lower chuck, and a 180-degree peel test was performed at a speed of 300 mm / min under an environment of 23 ° C and 50% RH. The peel force (N / cm) at this time was taken as the self-adhesive strength to the adherend (after accelerated test). <Adhesion stability> In measuring the above-mentioned "self-adhesion (after accelerated test)", the test pieces were visually inspected immediately after removal from the thermostatic chamber after the accelerated test to see if there was any lifting or peeling from the adherend, and were evaluated according to the following criteria. A: No lifting or peeling of the test piece from the substrate was observed. B: The test piece is observed to have lifted or peeled off from the substrate. <Reworkability> After measuring the above-mentioned "self-adhesive strength (after accelerated test)" (i.e., the adherend after the self-adhesive laminate had been peeled off), the surface of the adherend was visually inspected to see if any part of the self-adhesive foam sheet (acrylic resin) remained on it, and evaluated according to the following criteria. A: No resin residue is found on the surface of the substrate. B: Resin residue is found on the surface of the adherend.

[0062] Example 1 <Preparation of foam sheet composition> To a mixing vessel were added, in this order, 100 parts (solids: 55 parts) of an acrylic resin latex (Nipol LX874, manufactured by Nippon Zeon Co., Ltd., glass transition temperature: -36°C, solids concentration: 55%), 1 part of an epoxy-based crosslinking agent (Rikabond EX-8, manufactured by Japan Coating Resins Co., Ltd., fatty acid polyglycidyl ether), and 4 parts of a foam stabilizer (Nopco DC-100A, ammonium stearate, manufactured by San Nopco Ltd.) to obtain a composition for foam sheets. <Preparation of self-adhesive laminate> The composition for a foamed sheet obtained as described above was stirred with a whisk until the foaming ratio reached 1.6 times, and the stirring speed was further reduced and stirring was continued for 5 minutes. The foamed foam sheet composition (foam) was coated on a wallpaper substrate (Lilycolor Co., Ltd., "LB-9424") using an applicator. This was placed in a drying oven and held at 80°C for 1.33 minutes, 120°C for 1.33 minutes, and 140°C for 1.33 minutes to perform drying and crosslinking, thereby obtaining a self-adhesive laminate (laminate sheet) having a self-adhesive foam sheet on the substrate. The thickness of the self-adhesive foam sheet was 200 μm. The self-adhesive laminate thus obtained was subjected to various evaluations, the results of which are shown in Table 1.

[0063] Example 2 Except for changing the expansion ratio to 2.0 when preparing the self-adhesive laminate, a foam sheet composition and a self-adhesive laminate were prepared in the same manner as in Example 1, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0064] Comparative Example 1 Except for changing the expansion ratio to 1.0 when preparing the self-adhesive laminate, a foam sheet composition and a self-adhesive laminate were prepared in the same manner as in Example 1, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0065] Comparative Example 2 Except for changing the expansion ratio to 2.5 when preparing the self-adhesive laminate, a foam sheet composition and a self-adhesive laminate were prepared in the same manner as in Example 1, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0066] Comparative Example 3 <Preparation of acrylic resin (polymer)> A monomer mixture consisting of 64 parts of ethyl acrylate, 12 parts of 2-ethylhexyl acrylate, 12 parts of n-butyl acrylate, 9 parts of acrylonitrile, 2 parts of styrene and 1 part of acrylic acid, and 0.4 parts of sodium polyoxyethylene alkyl sulfate (Kao Corporation: Latemul E-118B) were mixed and stirred with 27.0 parts of deionized water to obtain a monomer emulsion. Next, a glass reaction vessel equipped with a reflux condenser, a dropping funnel, a thermometer, a nitrogen inlet, and a stirrer was prepared separately from the above, and 43.0 parts of deionized water and 0.2 parts of sodium polyoxyethylene alkyl sulfate were placed in this glass reaction vessel, and the temperature was raised to 80°C while stirring. Then, while maintaining the temperature at 80°C, 0.3 parts of ammonium persulfate dissolved in 5.7 parts of deionized water was added, and then the monomer emulsion obtained above was gradually added over 4 hours. After the addition was completed, stirring was continued for another 4 hours, and then the reaction was terminated by cooling to obtain a reaction mixture. The polymerization conversion rate at this time was almost 100% (98% or more), and the resulting reaction mixture was adjusted to pH 5.0 with 5% ammonia water, and 2.5 parts of polyoxyethylene lauryl ether (Kao Corporation: Emulgen 120) was added, followed by concentration to obtain a polymer latex with a solid content concentration of 55%. <Preparation of foam sheet composition> To a mixing vessel, 100 parts of the polymer latex, 3 parts of an epoxy-based crosslinking agent (Japan Coating Resins' "Rikabond EX-8", fatty acid polyglycidyl ether), 2 parts of a wax agent (containing a fatty acid ester having a fatty acid moiety with a carbon number of 16 to 34), and 4 parts of a foam stabilizer (San Nopco's "Nopco DC-100A", ammonium stearate) were added in this order. Finally, a thickener (Toagosei's "Aron A-20L", sodium polyacrylate) was added to adjust the viscosity to 4250 mPa s, thereby obtaining a foam sheet composition. <Preparation of self-adhesive laminate> The composition for a foamed sheet obtained as described above was stirred with a whisk until the foaming ratio reached 1.6 times, and the stirring speed was further reduced and stirring was continued for 5 minutes. The foamed foam sheet composition (foam) was coated on a wallpaper substrate (manufactured by Lilycolor Co., Ltd., "LB-9424") using an applicator. This was placed in a drying oven and held at 80°C for 1.33 minutes, 120°C for 1.33 minutes, and 140°C for 1.33 minutes to perform drying and crosslinking, thereby obtaining a self-adhesive laminate (laminate sheet) having a self-adhesive foam sheet on the substrate. The thickness of the self-adhesive foam sheet was 150 μm. The obtained self-adhesive laminate was then subjected to various evaluations. The results are shown in Table 1. When measuring the self-adhesive strength (initial and after accelerated testing), the test piece and the adherend peeled easily, making it impossible to measure the peel strength or evaluate the reworkability.

[0067] [Table 1]

[0068] It can be seen from Table 1 that the self-adhesive laminates of Examples 1 and 2 can simultaneously achieve high levels of conformability to irregularities during application, long-term adhesion stability, and reworkability after long-term use. On the other hand, Table 1 shows that Comparative Example 1, which has a high density and 25% compressive strength, has reduced conformability to irregularities during application and long-term adhesion stability, Comparative Example 2, which has a low density and 25% compressive strength, has reduced reworkability, and Comparative Example 3, which has a high 25% compressive strength, has reduced conformability to irregularities during application and long-term adhesion stability. [Industrial Applicability]

[0069] According to the present invention, it is possible to provide a self-adhesive laminate that simultaneously achieves high levels of conformability to irregularities during application, long-term adhesion stability, and reworkability after long-term use.

Claims

1. A self-adhesive laminate comprising a substrate and a self-adhesive foam sheet made of an acrylic resin foam, The acrylic resin foam is formed of a crosslinked acrylic resin, The self-adhesive laminate, wherein the self-adhesive foam sheet has a density of 0.4 g / cm 3 or more and 0.55 g / cm 3 or less and a 25% compressive strength of 3 kPa or more and 15 kPa or less.

2. 2. The self-adhesive laminate according to claim 1, wherein the average thickness of the self-adhesive foam sheet is 0.05 mm or more and 1 mm or less.

3. 3. The self-adhesive laminate according to claim 1, wherein the acrylic resin foam contains a foam stabilizer.

4. 4. The self-adhesive laminate according to claim 1, wherein the self-adhesive foam sheet has a conformability to unevenness of 30% or more and 90% or less.

5. 5. The self-adhesive laminate according to claim 1, wherein the initial self-adhesive strength of the self-adhesive foam sheet is 0.01 N / cm or more and 0.50 N / cm or less.

6. 6. The self-adhesive laminate according to claim 1, wherein the self-adhesive strength of the self-adhesive foam sheet after an accelerated test is 0.10 N / cm or more and 1.0 N / cm or less.

7. 7. The self-adhesive laminate according to claim 1, which is intended for attachment to an adherend surface having irregularities.

8. The acrylic resin contains 60% by mass or more and 95% by mass or less of (meth)acrylate monomer units.

8. The self-adhesive laminate according to claim 1, comprising the following proportions:

Citation Information

Patent Citations

  • Self-adhesive sheet and method for manufacturing the same

    JP2016125060A

  • Resin composition for self-sticking foamed sheet, self-sticking foamed sheet, and self-sticking foamed laminated sheet

    JP2016172805A

  • Graphic sheet and building structure

    JP2017218561A

  • Laminate sheet and manufacturing method of the laminate sheet

    JP2020062883A

  • Bubble-containing thermally-conductive resin-composition layer, manufacturing method therefor, and pressure-sensitive adhesive sheet using said resin-composition layer

    WO2012063935A1